Navigating Intellectual Property Challenges in Cross-Border Data Transfer (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In the contemporary global economy, cross-border data transfer has become integral to business operations, facilitating seamless information exchange worldwide. However, this practice brings forth complex intellectual property (IP) considerations that demand careful attention and strategic handling. This paper conducts a thorough exploration of the IP implications associated with cross-border data transfer, elucidating the intricate relationship between IP rights and the international movement of data. Specifically, the paper delves into trademark-related issues in cross-border data transfer, including trademark registration, enforcement strategies, and measures to mitigate infringement risks across diverse legal jurisdictions. It also addresses the protection of trade secrets and confidential information, highlighting the challenges posed by data transfer and advocating for the adoption of effective safeguarding measures. Furthermore, the paper analyzes the role of technological protection measures, such as digital rights management (DRM), in preserving intellectual property during data transfer, while considering pertinent legal and ethical considerations. By providing nuanced insights into these IP implications, this paper offers valuable guidance for policymakers, legal professionals, businesses, and other stakeholders engaged in cross-border data exchange endeavors.